A Harnack Inequality for Degenerate Parabolic Equations (Journal of Partial Differential Equations, 2020)
In this paper we apply the Moser iteration method to degenerate parabolic divergence structure equations. Under some conditions we get a Harnack inequality for weak solutions and from it derive H&#246lder estimates for weak solutions of uniformly degenerate parabolic equations and the continuity of weak solutions of non-uniformly degenerate parabolic equations.